2011
DOI: 10.1007/s11229-011-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Words or deeds? Choosing what to know about others

Abstract: Social cooperation often relies on individuals' spontaneous norm obedience when there is no punishment for violation or reward for compliance. However, people do not consistently follow pro-social norms. Previous studies have suggested that an individual's tendency toward norm conformity is affected by empirical information (i.e. what others did or would do in a similar situation) as well as by normative information (i.e. what others think one ought to do). Yet little is known about whether people have an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Given the sensitivity of expectations to the information regarding other's behaviors or beliefs, Xiao and Bicchieri (2009) conducted a follow-up study examining whether dictators, before making decisions, have intrinsic motivation to seek norm-revealing information (i.e., what other dictators would do or think ought to be done). They found that dictators do not avoid the information when it is free, yet they are not willing to incur even very small costs to obtain the information.…”
Section: Expectations Norms and Context Effects In Dictator Gamesmentioning
confidence: 99%
“…Given the sensitivity of expectations to the information regarding other's behaviors or beliefs, Xiao and Bicchieri (2009) conducted a follow-up study examining whether dictators, before making decisions, have intrinsic motivation to seek norm-revealing information (i.e., what other dictators would do or think ought to be done). They found that dictators do not avoid the information when it is free, yet they are not willing to incur even very small costs to obtain the information.…”
Section: Expectations Norms and Context Effects In Dictator Gamesmentioning
confidence: 99%
“…Methodologically, we find asking participants to pay for the information (vs. not) does not moderate the difference in the level of altruistic behavior observed between treatments. Theoretically, costly information should deter participants from obtaining information (Leib, 2023; Saccardo & Serra-Garcia, 2020; Xiao & Bicchieri, 2011). Moreover, evidence from individual studies shows even small barriers to willful ignorance, such as the need to overcome a default setting, have strong effects on information seeking (Grossman, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, normative broadly implies a social pressure through which norms are maintained, promoted, or enforced. A practice, institution, or ideal of a group is normative if it serves to regulate the acceptable limits of tolerance by which to evaluate conformity or nonconformity with the preferential norm [5,58,[61][62][63][64][65][66][67]. Under these definitions, normative would signify the overall set of ideals that regulate norms, whereas norms would be bounded by that set of normative constraints.…”
Section: (Re-)defining the Problem Of Normsmentioning
confidence: 99%
“…The formation and causal relationship questions related to social norms present significant theoretical and methodological problems, especially towards the implementation of social norm interventions (e.g., [15,47,101,103,[105][106][107]). Quite often, what people report that they believe they should do does not match what they actually do in observed behavior [3,65,108]. This raises additional questions regarding the theorization of norm compliance [48,109,110], such as the status and force of norm internalization (e.g., [111][112][113][114][115][116]) or the role of external enforcement (see [45,114,[117][118][119][120]).…”
Section: (Re-)defining the Problem Of Normsmentioning
confidence: 99%